ANALISIS PENERAPAN METODE FULL COSTING PADA UD RATNA JAYA PROBOLINGGO - Seger, Seger Priantono; Elok Dwi Vidiyastutik (Pusat Riset dan Inovasi Nasional, 2022)
This research was conducted at UD Ratna Jaya Probolinggo which is engaged in the dry noodle food product industry, with the aim of knowing the calculation of the cost of production at UD Ratna Jaya and to analyze the application of the full costing method for the calculation of the cost of goods on UD Ratna Jaya Probolinggo. This type of research uses quantitative descriptive research. Data is collected by documentation, data analysis methods in the form of descriptive analysis. The results showed that UD Ratna Jaya still uses a simple method of calculating the cost of production by summing up production costs consisting of raw material costs, direct labor costs, and supporting costs. The application of the full costing method by detailing all production costs that occur including raw material costs, direct labor costs, and factory overhead costs, can determine the amount of cost of production more accurately.